MicroRNAs in lung cancer - Castro, Diana (2018)
Lung cancer (LC) is a serious public health problem responsible for the majority of cancer deaths and comorbidities in developed countries. Tobacco smoking is considered the main risk factor for LC; however, only a few smokers will be affected by this cancer. Current screening methods are focused on identifying the early stages of this malignancy. Thus, new data concerning the roles of microRNA alterations in inflammation, epithelial-mesenchymal transition and lung disease have increased hope about LC pathogenesis, diagnosis, treatment and prognosis. MicroRNA mechanisms include angiogenesis promotion, cell cycle regulation by modulating cellular proliferation and apoptosis, and migration and invasion inhibition. In this context, this manuscript reviews the current information about many important microRNAs as they relate to the initiation and progression of LC.